2008
DOI: 10.1007/s11999-008-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crosslinked Polyethylene is Safe for Use in Total Knee Arthroplasty

Abstract: Highly cross-linked polyethylene (XLPE) has been used with good initial success in hip arthroplasty to reduce wear. However, the process of crosslinking reduces fracture toughness, raising concerns as to whether it can be safely used in total knee arthroplasty (TKA). We therefore asked whether XLPE can be used safely in TKA. We performed a retrospective review of 100 subjects receiving XLPE and compared them to 100 subjects who received standard polyethylene in the setting of TKA. The standard polyethylene gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 42 publications
2
64
1
Order By: Relevance
“…Thus, concerns about the minimum thickness of polyethylene are currently perceived to limit the introduction of acetabular liners with femoral head sizes greater than 48 mm. This systematic review identified numerous studies documenting the clinical performance of HXLPEs for hip arthroplasty, but only two clinical outcomes studies were identified for HXLPE use in the knee [62,99]. The authors of both knee studies emphasized their research demonstrated the short-term safety of HXLPE in the knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, concerns about the minimum thickness of polyethylene are currently perceived to limit the introduction of acetabular liners with femoral head sizes greater than 48 mm. This systematic review identified numerous studies documenting the clinical performance of HXLPEs for hip arthroplasty, but only two clinical outcomes studies were identified for HXLPE use in the knee [62,99]. The authors of both knee studies emphasized their research demonstrated the short-term safety of HXLPE in the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Only two knee studies were identified in the literature search of HXLPEs in total joint arthroplasty [62,99], * Values are expressed as mean, with standard error in parentheses; 2D = two-dimensional; HXLPE = highly crosslinked polyethylene; RCT = randomized controlled trial; COH = prospective or retrospective cohort study.…”
Section: Summary Of Radiographic Outcome Studies For Hxlpes In Knee Amentioning
confidence: 99%
See 1 more Smart Citation
“…The first clinical study of crosslinked polyethylene was published by Hodrick et al (2008), and they reported a consecutive series of 200 Natural Knee II systems (Zimmer), comparing the first 100 cases to receive crosslinked polyethylene with the previous 100 cases using non-crosslinked polyethylene. The crosslinked polyethylene group had an average age of 67, and was followed for a minimum of 69 months, as compared to an average age of 70 and a minimum follow-up of 82 months for the non-crosslinked group.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced wear was also found in crosslinked polyethylene when subjected to diverse wear models with a scratched femoral component or an unbalanced knee (Muratoglu et al 2002, 2004, Hermida et al 2008). There have, however, only been a few reports of the clinical results of highly crosslinked polyethylene in TKA (Hodrick et al 2008, Minoda et al 2009, Long et al 2012). While these studies have shown no difference in clinical or radiographic outcomes when comparing crosslinked polyethylene with non-crosslinked polyethylene, the longest follow-up was 7 years.…”
mentioning
confidence: 99%